(untitled) (International Journal of Environmental Sciences, 2025)
Water resources are a critical component of regional development, especially in areas experiencing rapid land-use changes. Assessing both the quantity and quality of water is essential to ensure long-term environmental sustainability and human well-being. This study aims to assess the water carrying capacity and pollution load in the Tiku Sub-Watershed, located in Musi Rawas Utara Regency, Indonesia. The evaluation combines hydrological availability analysis with water quality assessment to determine the balance between water supply and its environmental sustainability. The results reveal a paradoxical condition: although the annual surface water availability is abundant, reaching approximately 96.13 million m³ with a dependable flow rate of 3.05 m³/s, the water quality is critically degraded. Pollution indices show an average score of 6.65, indicating moderate pollution status. Laboratory analyses of eight sampling points indicate that concentrations of mercury (Hg), cadmium (Cd), phosphate (PO₄³⁻), and ammonia (NH₃) consistently exceed the national water quality standards. None of the observed locations meet the permissible thresholds, demonstrating a severely limited assimilative capacity of the aquatic environment. Water demand is primarily driven by land-based economic activities (98.26%), while domestic use accounts for only 1.74%. The carrying capacity index (criticality ratio) is 0.12, suggesting that current water use remains within sustainable limits. However, the low assimilative capacity underscores urgent concerns for pollution control and integrated watershed management. These findings highlight the necessity for stricter regulation of pollutant sources and sustainable land use practices to protect water resources in the Tiku Sub-Watershed.